2013
DOI: 10.1177/2047981613512484
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of apparent diffusion coefficient for the accurate assessment and differentiation of intracranial meningiomas

Abstract: BackgroundDiffusion-weighted imaging (DWI) along with the calculation of apparent diffusion coefficient (ADC), is a novel, non-invasive, and reliable technique of choice for accurate assessment and for the treatment planning of different types of brain tumors. It is more advantageous in the distinction and differentiation of benign from malignant meningiomas on the basis of ADC values.PurposeTo investigate the utility of DW magnetic resonance imaging (MRI), and to compare the apparent diffusion coefficient (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
4
22
1
1
Order By: Relevance
“…6 Many studies have reported that the mean ADC values of benign meningioma are higher than the mean ADC values of atypical/malignant meningioma. 2,[5][6][7]9 Our results were in agreement with previous studies that report a significant statistical difference in ADC value of atypical / malignant and benign meningiomas. 2,[5][6][7]10 The mean ADC value of atypical and malignant meningiomas in our study was significantly lower compared with that of benign meningiomas (0.698 x 10 -3 mm 2 /s ± 0.06 x 10 -3 mm 2 /s vs. 0.83 x 10 -3 mm 2 /s ± 0.37 x 10 -3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…6 Many studies have reported that the mean ADC values of benign meningioma are higher than the mean ADC values of atypical/malignant meningioma. 2,[5][6][7]9 Our results were in agreement with previous studies that report a significant statistical difference in ADC value of atypical / malignant and benign meningiomas. 2,[5][6][7]10 The mean ADC value of atypical and malignant meningiomas in our study was significantly lower compared with that of benign meningiomas (0.698 x 10 -3 mm 2 /s ± 0.06 x 10 -3 mm 2 /s vs. 0.83 x 10 -3 mm 2 /s ± 0.37 x 10 -3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 93%
“…Heterogeneous enhancement and irregular cerebral surface that may help differentiate the two groups 4 are still not consistent and unique neuroimaging features for diagnosing malignant meningiomas. 5 Diffusion-weighted imaging (DWI) along with the calculation of apparent diffusion coefficient (ADC) have been reported to be a non-invasive and reliable technique in the distinction and differentiation of benign from malignant / atypical meningiomas on the basis of ADC maps and ADC value. 2,[5][6][7] Most publications, however, calculated ADC value on a separate specialised workstation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artmış mitotik aktivite, nekroz, yüksek nükleus sitoplazma oranı ve kesintisiz hücre büyümesi yüksek dereceli menenjiomlarda izlenir ki bu da kısıtlanmış su difüzyonu ve düşük ADC değerleri ile sonuçlanır [2]. Bununla birlikte bazı çalışmalarda atipik/malign menenjiomlarda benign menenjiomlara göre daha düşük ADC değerleri izlenmişken bazı çalışmalarda anlamlı farklılık saptanmamıştır [36][37][38][39][40][41][42]. Ayrıca menenjiomlarda yüksek dereceli gliomlara göre düşük ADC izlenir [18].…”
Section: Menenjiomunclassified